Studies on Groundwater Problems in an Area Subjected to Sea Water Ingression and Seepage Into Groundwater in Karaikal District Using GIS - Subramani, T; Krishnan, P (International Journal of Engineering and Technology, 2018)
Fresh groundwater quality and accessibility in coastal zones is influenced via seawater interruption into coastal aquifers, and coastal water quality and biological community status might be altogether influenced by groundwater pollutants that are transported into coastal waters by submarine groundwater discharge (SGD). SGD and its pertinent evaluation as one associating part  among the different principle local pathways of freshwater and tracer/poison contributions from land to sea and the coordinated framework working of both and as primary segments of the same coastal groundwater framework. An elective technique might be to control seawater interruption through fake groundwater revive, for example by adequately treated wastewater, which may impressively decrease long haul patterns of saltiness increment in pumped groundwater, notwithstanding for little simulated energize rates contrasted with pumping rates. Both the outside sources and the interior wellsprings of water seepage might be distinguished via doing infrared thermo-realistic assessments subsequent to directing water snugness tests, flooding tests or pressure driven tests as suitable. A contextual investigation was led to discover the examinations on groundwater issues in a region subjected to sea water ingression and seepage into groundwater in Karaikal